THE TYPES OF HOOGERWERFâ€™S NEW TAXA OF BIRDS IN THE COLLECTION OF THE MUSEUM ZOOLOGICUM BOGORIENSE, CIBINONG SCIENCE CENTRE BOGOR, INDONESIA - Sudaryanti Sudaryanti; S. Somadikarta; Darjono Darjono (BRIN Publishing (Penerbit BRIN), 2006)
From 1962 to 1967 Hoogerwerf described 16 new taxa of birds fromJava and its satellite islands. His description of each new taxon was based on 3 to 34 specimens. Despite the regulations of the International Code of Zoological Nomenclature (ICZN), which clearly stipulated to designate the type specimens, Hoogerwerf had designated two and in one case three â€œtypeâ€ specimens for each of the 14 out of his 16 new taxa, instead. In order to preserve stability of nomenclature, we reevaluate and designate the paratypes, lectotypes, paralectotypes of these Hoogerwerfâ€™s new taxa. These type specimens are deposited in the collections of MZB.